The Association Between Tobacco Retailer Outlet Density and Prevalence of Cigarette Smoking in Virginia. Issue 1 (25th June 2022) - Lin, Shuo-yu; Zhou, Weiyu; Koch, J Randy; Barnes, Andrew J; Yang, Ruixin; Xue, Hong
Abstract: Objective: We examine the association between tobacco retail outlet density and adult smoking prevalence at the county level in Virginia, controlling for spatial autocorrelations. Aims and Methods: Pooling data from 2020 County Health Rankings (compiled data from various sources including, but not limited to, the National Center for Health Statistics—Mortality Files, the Behavioral Risk Factor Surveillance System (BRFSS), and the American Community Survey) and Counter Tools, we conducted regression analyses that accounted for spatial autocorrelation (spatial lag models, LMlag) and adjusted for county-level access to healthcare, demographics, SES, environmental factors, risk conditions or behaviors, and population health measures. Results: Our estimates provide evidence that every increase of one tobacco retail outlet per 1000 persons was associated with 1.16 percentage points (95% CI: 0.80–1.52) higher smoking prevalence at the county level in Virginia after controlling for spatial autocorrelation. The effect of outlet density was largely explained by social determinants of health such as SES, risky conditions or behaviors, and environmental factors. We further noticed that the impact of social determinants of health were closely related and can be explained by indicators of population health (rates of mental distress (β = 1.49, 95% CI: 1.31–1.67) and physical inactivity (β = 0.07, 95% CI: 0.04–0.10). Conclusions: Although higher tobacco outlet density was associated with an increase in county-level smoking prevalence, the impact of outlet density was largely explained by social determinants of health and mental illness. Improving well-being at the community level could be a promising strategy in future tobacco control policies. Implication: The influence of tobacco outlet density seems to be explained by other social determinants of health and population level of mental or physical health. Thus, efforts to reduce tobacco use and consequent negative health effects should explore the impact of improving regional living standards. However, a sole focus on economic growth may not be sufficient, whereas a focus on such things as promoting work-life balance and improving overall well-being at the community level may be more